Constructions of spectral triples on C*-algebras - Hawkins, Andrew (2013)
We present some techniques in the construction of spectral triples for C*-algebras, in particular those which determine a compatible metric on the state space, which provides a noncommutative analogue of geodesic distance between points on a manifold.